Energy and sustainable development in Latin America and the Caribbean. In: Energy magazine, v. 23, no. 1, p. 22-28. (2011)
An overview of the achievements with regard to sustainability, the opportunities, the shortages and policy trends. Explore what can be done to improve the situation and presents guidelines for an energy policy aimed at ensuring sustainable development.
Keywords: ENERGY; ENERGY POLICY; SUSTAINABLE DEVELOPMENT; LATIN AMERICA; CARIBBEAN